Faktor-faktor yang Mempengaruhi Indeks Persaingan Pariwisata Perjalanan - Benny Tjandrasa; Andrew Sebastian Lehman; Mayang Permata Sari; Sheilla Rizqia Ardhani (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
In an effort to improve the image of tourism that will have an impact on increasing the number of tourists, the Indonesian government wants to increase the travel tourism competitiveness index. On the other hand, the risk of natural damage due to human actions and also fluctuations in the number of visitors due to the tight competition between countries is a threat to the tourism industry. In an effort to achieve sustainable tourism, the application of the latest information and communication technology is a solution to keep attracting visitors and will simultaneously maintain environmental sustainability. So far Indonesia excels in the assessment of price competitiveness, while for the assessment of information and communication technology readiness Indonesia has not been considered superior. This research was conducted with a descriptive-explanatory study approach. Using simple random sampling, samples in the form of secondary data from seven ASEAN countries from 2007 to 2019 were processed using multivariable regression to assess the magnitude of influence and significance levels of the various variables studied. The results showed that price competitiveness didn’t have a significant effect on the travel tourism competitiveness index in the ASEAN countries but there were two other factors that had a significant effect.